2004
DOI: 10.1111/j.0030-1299.2005.13277.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of salmon‐derived nitrogen by mosses and liverworts in coastal British Columbia

Abstract: Throughout forested watersheds bordering the North Pacific, anadromous salmon (Oncorhynchus spp. ) are transferred into coastal forests by numerous predators and scavengers with remnants providing an important nutrient subsidy to riparian zones. The contribution of these nutrients to mosses and liverworts, which are the dominant ground cover of coastal forests, has not been investigated. We examine here d 15 N isotope signatures and foliar percent N of eight moss and liverwort species, as well as moss and live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 63 publications
(114 reference statements)
1
39
0
Order By: Relevance
“…Although ChS cease feeding after entering freshwater (Healey 1991; this study), they can impact aquatic, riverine, and terrestrial ecosystems through the nutrients released on their death (Soto and Campos 1995;Soto et al 2007) as well as parasites from the ocean (the macro-parasite fauna found in our field survey is described in Bravo 2005). Input of marine-derived nutrients may result in increased basal food web production (Zhang et al 2003;Wilkinson et al 2005), and cascade to upper trophic levels (Bilby et al 1998). These are only a few simple examples of how ChS invasion may impact local ecosystems.…”
Section: Overview On Expected Consequencesmentioning
confidence: 99%
“…Although ChS cease feeding after entering freshwater (Healey 1991; this study), they can impact aquatic, riverine, and terrestrial ecosystems through the nutrients released on their death (Soto and Campos 1995;Soto et al 2007) as well as parasites from the ocean (the macro-parasite fauna found in our field survey is described in Bravo 2005). Input of marine-derived nutrients may result in increased basal food web production (Zhang et al 2003;Wilkinson et al 2005), and cascade to upper trophic levels (Bilby et al 1998). These are only a few simple examples of how ChS invasion may impact local ecosystems.…”
Section: Overview On Expected Consequencesmentioning
confidence: 99%
“…Along with other pathways of salmon nutrient entry into terrestrial food webs, such as flooding and hyporheic water flow, salmon subsidies may ultimately affect riparian plant diversity (Wilkinson et al 2005;Hocking and Reynolds 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nutrient release from carcasses can influence plant growth and community structure (Wilkinson et al 2005;Drake and Naiman 2007), while diet shifts to salmon in consumers can alter predator-prey dynamics (Darimont et al 2008) and rates of detrital processing (Zhang et al 2003). Terrestrial insect groups such as blowflies (Calliphoridae) and burying beetles (Silphidae) also increase processes of salmon decomposition and nutrient distribution in forest riparian zones (Jauquet et al 2003;Meehan et al 2005;.…”
Section: Introductionmentioning
confidence: 99%